Increased generalized anxiety, depression and distress during the COVID-19 pandemic: a cross-sectional study in Germany - Bäuerle, Alexander; Teufel, Martin; Musche, Venja; Weismüller, Benjamin; Kohler, Hannah; Hetkamp, Madeleine; Dörrie, Nora; Schweda, Adam; Skoda, Eva-Maria (Journal of public health (Oxford, England), 2020)
Since the first cases of the novel coronavirus disease SARS-CoV-2 were reported in December 2019 in China, the virus has spread in most countries. The aim of the present study was to assess initial data on the mental health burden of the German public during the COVID-19 pandemic. A cross-sectional study was conducted in Germany and collected complete datasets from 15 704 German residents aged 18 years and over. Besides demographics, generalized anxiety (GAD-7), depression (PHQ-2) and psychological distress (DT) were assessed. Furthermore, COVID-19-related fear, trust in governmental actions to face COVID-19 and the subjective level of information regarding COVID-19 were covered. Significantly increased symptoms were highly prevalent in all dimensions: generalized anxiety (44.9%), depression (14.3%), psychological distress (65.2%) and COVID-19-related fear (59%). Females and younger people reported higher mental burden. Trust in governmental actions to face COVID-19 and the subjective level of information regarding COVID-19 are negatively associated with mental health burden. However, the subjective level of information regarding COVID-19 is positively associated with increased COVID-19-related fear. The provision of appropriate psychological interventions for those in need and the provision of transparency and comprehensible information are crucial during the current pandemic.